(untitled) (Eurasian Journal of Humanities and Social Sciences, 2023)
The study of personalities is one of the important studies that unveils a unique personality in our Islamic and civilized heritage, and among these important personalities, Yusuf bin Hassan bin Abd al-Hadi al-Hanbali, known as Ibn al-Mubarrad (d.: 856 AH / 1452 AD), who had a great role In the scientific movement in the ninth century AH, which was characterized by an abundance of authorship, as it reached a great value, and I found a lot of it, and I found some of it, you see the light, so I wrote this research to reveal the personality of this expert science in the types of science, and the reference is part of his writings, with mentioning his contributions to the biography of the Prophet and came Research, objectives, preface, and the first topic: Introducing Jamal al-Din Ibn al-Mubarrad, his name, lineage, and upbringing, his scholarly life and doctrine, his scholarly journeys and elders, his works, his scholarly stature and the scholars’ praise for him, the positions he held, his relationship with authority, and his death, and its authoring methodology, conclusion and results, and finally a list of sources and references